Sequence-based nomenclature: a reply to Thines et al. and Zamora et al. and provisions for an amended proposal “from the floor” to allow DNA sequences as types of names - Lücking, Robert (IMA Fungus, 2018)
We reply to two recently published, multi-authored opinion papers by opponents of sequence-based nomenclature, namely Zamora et al. (IMA Fungus 9: 167–175,2018) and Thines et al. (IMA Fungus 9: 177–183, 2018). While we agree with some of the principal arguments brought forward by these authors, we address misconceptions and demonstrate that some of the presumed evidence presented in these papers has been wrongly interpreted. We disagree that allowing sequences as types would fundamentally alter the nature of types, since a similar nature of abstracted features as type is already allowed in the Code (Art. 40.5), namely an illustration. We also disagree that there is a high risk of introducing artifactual taxa, as this risk can be quantified at well below 5 %, considering the various types of high-throughput sequencing errors. Contrary to apparently widespread misconceptions, sequence-based nomenclature cannot be based on similarity-derived OTUs and their consensus sequences, but must be derived from rigorous, multiple alignment-based phylogenetic methods and quantitative, single-marker species recognition algorithms, using original sequence reads; it is therefore identical in its approach to single-marker studies based on physical types, an approach allowed by the Code. We recognize the limitations of the ITS as a single fungal barcoding marker, but point out that these result in a conservative approach, with “false negatives” surpassing “false positives”; a desirable feature of sequence-based nomenclature. Sequence-based nomenclature does not aim at accurately resolving species, but at naming sequences that represent unknown fungal lineages so that these can serve as a means of communication, so ending the untenable situation of an exponentially growing number of unlabeled fungal sequences that fill online repositories. The risks are outweighed by the gains obtained by a reference library of named sequences spanning the full array of fungal diversity. Finally, we elaborate provisions in addition to our original proposal to amend the Code that would take care of the issues brought forward by opponents to this approach. In particular, taking up the idea of the Candidatus status of invalid, provisional names in prokaryote nomenclature, we propose a compromise that would allow valid publication of voucherless, sequence-based names in a consistent manner, but with the obligate designation as “nom. seq.” (nomen sequentiae). Such names would not have priority over specimen- or culture-based names unless either epitypified with a physical type or adopted for protection on the recommendation of a committee of the International Commission on the Taxonomy of Fungi following evaluation based on strict quality control of the underlying studies based on established rules or recommendations.